Intraperitoneally Delivered Mesenchymal Stem Cells Alleviate Experimental Colitis Through THBS1-Mediated Induction of IL-10-Competent Regulatory B Cells - Liu, Jialing; Lai, Xingqiang; Bao, Yingying; Xie, Wenfeng; Li, Zhishan; Chen, Jieying; Li, Gang; Wang, Tao; Huang, Weijun; Ma, Yuanchen; Shi, Jiahao; Zhao, Erming; et al. (Frontiers in Immunology, 2022)
Mesenchymal stem cells (MSCs) show promising therapeutic potential in treating inflammatory bowel disease (IBD), and intraperitoneal delivery of MSCs has become a more effective route for IBD treatment. However, the underlying mechanisms are still poorly understood. Here, we found that intraperitoneally delivered MSCs significantly alleviated experimental colitis. Depletion of peritoneal B cells, but not macrophages, clearly impaired the therapeutic effects of MSCs. Intraperitoneally delivered MSCs improved IBD likely by boosting the IL-10 producing B cells in the peritoneal cavity, and a single intraperitoneal injection of MSCs could significantly prevent disease severity in a recurrent mouse colitis model, with lower proinflammation cytokines and high level of IL-10. The gene expression profile revealed that thrombospondin-1 (THBS-1) was dramatically upregulated in MSCs after coculture with peritoneal lavage fluid from colitis mice. Knockout of THBS-1 expression in MSCs abolished their therapeutic effects in colitis and the induction of IL-10-producing B cells. Mechanistically, THBS-1 modulates the activation of transforming growth factor-β (TGF-β), which combines with TGF-β receptors on B cells and contributes to IL-10 production. Blocking the interaction between THBS-1 and latent TGF-β or inhibiting TGF-β receptors (TGF-βR) significantly reversed the THBS-1-mediated induction of IL-10-producing B cells and the therapeutic effects on colitis. Collectively, our study revealed that intraperitoneally delivered MSCs secreted THBS-1 to boost IL-10+Bregs and control the progression and recurrence of colitis, providing new insight for the prevention and treatment of IBD.